Kinetic evidence for the influence of subsurface oxygen on palladium surfaces towards CO oxidation at high temperatures - Gopinath, Chinnakonda S.; Thirunavukkarasu, Kandasamy; Nagarajan, Sankaranarayanan (Chemistry-an Asian Journal, 2009)
Transient state kinetics of the catalytic oxidation of CO with 0, on Pd-surfaces has been measured under isothermal conditions by using a molecular beam approach. Systematic studies were carried out as a function of reaction temperature and CO+O(2) composition. With sufficient kinetic evidence, we have demonstrated the positive influence of subsurface oxygen towards CO-adsorption and oxidation to CO, at high temperatures (600-900 K) on Pd-surfaces, and the likely electronic nature of the surface changes with oxygen in the subsurface. These studies also provide a direct proof for CO-adsorption with a significantly reactive sticking coefficient at high temperatures on Pd-surfaces exhibiting a significant subsurface O-coverage.
Keywords: Adsorption; kinetics; Oxidation; Palladium; surface analysis